The Dividend Payment Puzzle - Fauziah, Fenty; Jamal, Sri Wahyuni; Rashid, Umi Kartini (EKOMABIS: Jurnal Ekonomi Manajemen Bisnis, 2024)
This study's objective is to ascertain and identify influencing the decision to pay dividends. Dividend data were subjected to fixed effects model. Panel regression analysis taken from annual reports issued by manufacturing companies listed on the BEI above 2016-2022 period. The affect dividends are ROA, DER, Size and TR. The company must pay attention to the overall factor that used, so that policies can be taken appropriately. Dividend payments are concentrated in large companies. Managers can use the empirical findings to make dividend payment decisions. The government learn from the impact of changes to the Job Creation Law and Income Tax Law, so that Indonesia becomes an investment destination. The dividend puzzle needs close attention to the different characteristics of firms in explanations for paying dividends.